2022
DOI: 10.1038/s41433-022-01985-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of the paramedian forehead flap alone or in combination with other techniques in the reconstruction of periocular defects and orbital exenterations

Abstract: Purpose The paramedian forehead flap (PMFF) is a reconstructive option for large eyelid defects and orbital exenterations. We report a series of cases where PMFF reconstruction was carried out at various institutions in Australia. Methods This study was a multi-centre, retrospective, non-comparative case series investigating the clinical outcomes of the PMFF for reconstructing periocular defects and orbital exenterations. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Lower eyelid repair aims to preserve functional elements, including maintaining an intact tear-corneal rim and eye closure, avoiding blocking the visual field, reducing scarring, and, if possible, meeting aesthetic requirements by hiding scars. Direct closure, 24 skin grafting, 25 the Tenzel semicircular flap, 11 the McGregor flap, 26 the Hughes tarsoconjunctival flap, 12 the Mustarde cheek rotational flap, 27 the Fricke’s flap, 28 the forehead flap, 29 and the tripier flap, 30 which are frequently used, do not meet these criteria. Another drawback is that significant expertise is required to select the right approach based on the size and location of the defect in all procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Lower eyelid repair aims to preserve functional elements, including maintaining an intact tear-corneal rim and eye closure, avoiding blocking the visual field, reducing scarring, and, if possible, meeting aesthetic requirements by hiding scars. Direct closure, 24 skin grafting, 25 the Tenzel semicircular flap, 11 the McGregor flap, 26 the Hughes tarsoconjunctival flap, 12 the Mustarde cheek rotational flap, 27 the Fricke’s flap, 28 the forehead flap, 29 and the tripier flap, 30 which are frequently used, do not meet these criteria. Another drawback is that significant expertise is required to select the right approach based on the size and location of the defect in all procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found no statistically significant correlation between diabetes and flap success ( 13 ). There are studies proving that successful flap division could occur within 1–2 weeks despite any underlying comorbidities ( 15 ). In our study, the absence of flap necrosis in any of the patients indicates that with strong and sufficient vascular support, it can be successfully used even in full-thickness defects.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] While there have been few studies in the literature describing reconstruction with PMFF and surgical outcomes, there have been no studies describing symmetry outcomes of PMFF reconstruction of the periocular region. 12,13 In the current study, we aim to describe reconstruction of the medial periocular region with the paramedian forehead flap (PMFF). The medial canthus is not only anatomically important for the lacrimal drainage system but also presents at a fixed distance from the facial midline, which is important for cosmetic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The paramedian forehead flap has traditionally primarily been used in the reconstruction of nasal defects and has not been extensively studied in reconstruction of periorbital defects 9–11 . While there have been few studies in the literature describing reconstruction with PMFF and surgical outcomes, there have been no studies describing symmetry outcomes of PMFF reconstruction of the periocular region 12,13 …”
Section: Introductionmentioning
confidence: 99%